A global analysis of bidirectional interactions in alpine plant communities shows facilitators experiencing strong reciprocal fitness costs. Issue 1 (12th December 2013) - Schöb, Christian; Michalet, Richard; Cavieres, Lohengrin A.; Pugnaire, Francisco I.; Brooker, Rob W.; Butterfield, Bradley J.; Cook, Bradley J.; Kikvidze, Zaal; Lortie, Christopher J.; Xiao, Sa; Al Hayek, Patrick; Anthelme, Fabien; et al.
Summary: Facilitative interactions are defined as positive effects of one species on another, but bidirectional feedbacks may be positive, neutral, or negative. Understanding the bidirectional nature of these interactions is a fundamental prerequisite for the assessment of the potential evolutionary consequences of facilitation. In a global study combining observational and experimental approaches, we quantified the impact of the cover and richness of species associated with alpine cushion plants on reproductive traits of the benefactor cushions. We found a decline in cushion seed production with increasing cover of cushion‐associated species, indicating that being a benefactor came at an overall cost. The effect of cushion‐associated species was negative for flower density and seed set of cushions, but not for fruit set and seed quality. Richness of cushion‐associated species had positive effects on seed density and modulated the effects of their abundance on flower density and fruit set, indicating that the costs and benefits of harboring associated species depend on the composition of the plant assemblage. Our study demonstrates 'parasitic' interactions among plants over a wide range of species and environments in alpine systems, and we consider their implications for the possible selective effects of interactions between benefactor and beneficiary species. Abstract : See also the Commentary by McIntire